Hubungan Makroekonomi dan Psikologi Investor Terhadap Resiko Pengambilan Keputusan Investasi Saham - Alfian Yudha Sasongko; Sapto Jumono; Eka Bertuah (Universitas Muhammadiyah Tangerang, 2022)
This study aim to determine the relationship between psychological factors (risk perception, herding and overconfidence) and macroeconomic factors (inflation, interest rate and exchange rate) on investment decision making. Population in this study was 150 respondents investor in Jakarta using purposive sampling with criteria investor being at least 17 years old. Distribution of questionnaires to respondent using google from to carry out processing of collecting respondent data with multiple linier regression analysis techniques using SPSS (Statical Package for the Socials Science). The result of this research indicate that psychological factor overconfidence has positive and significant effect on investment decision making, while herding has a positive and insignificant effect on investment decision making. This affect the intention and belief in making investment decisions making based on theory reasoned action